2005
DOI: 10.1292/jvms.67.145
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Antigenic Analyses of Bovine Respiratory Syncytial Virus Detected in Japan

Abstract: ABSTRACT. Genetic and antigenic analyses of bovine respiratory syncytial virus were conducted on 12 field strains from Tohoku and Hokuriku districts in Japan during from 2002 to 2004. On the phylogenetic tree of the nucleotide sequences of the glycoprotein region, the examined strains fell in the same cluster as the strain isolated in Nebraska and were classified as the subgroup III. The examined strains were subdivided into 2 lineages (A, B). Isoleucine 200 of the epitope domain was replaced by threonine as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 19 publications
(32 reference statements)
1
14
2
4
Order By: Relevance
“…The existence of six genetic subgroups based on G and of five based on F or N has also been established [150]. This classification showed a spatial clustering of BRSV isolates that has been confirmed by studies including isolates collected in many countries [126,154,170]. The degree of genetic variability of BRSV is limited being less than 15%, which is less than that observed within one subgroup of HRSV [105].…”
Section: Antigenic and Genetic Subgroups Of Brsvmentioning
confidence: 69%
“…The existence of six genetic subgroups based on G and of five based on F or N has also been established [150]. This classification showed a spatial clustering of BRSV isolates that has been confirmed by studies including isolates collected in many countries [126,154,170]. The degree of genetic variability of BRSV is limited being less than 15%, which is less than that observed within one subgroup of HRSV [105].…”
Section: Antigenic and Genetic Subgroups Of Brsvmentioning
confidence: 69%
“…Given the high sequence identity (98-100%) among the Czech strains and the importation of breeding animals from several countries including Denmark, the authors suggested animal trade as a possible transmission route. Phylogenetic analyses of BRSV have also been reported in other countries quite recently, including Poland [17], the UK [18], and Japan [19].…”
Section: Introductionmentioning
confidence: 83%
“…These observations suggested the continuous modification of the highly conserved central region of the immunodominant G protein, thus highlighting the importance of considering BRSV evolution in the rational development of vaccines [50]. Overall, this work could be considered as the foundation of modern BRSV molecular epidemiology, it has also established the basis for subsequent studies looking at the molecular epidemiological patterns of BRSV infection in different geographical regions [37,56,76,77]. …”
Section: Molecular Epidemiology and Evolution Of Brsvmentioning
confidence: 95%